2021
DOI: 10.1002/pssr.202000608
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Response of Encapsulated Oxygen‐Containing Yttrium Hydride Thin Films

Abstract: Photochromic oxygen-containing yttrium-hydride thin films are synthesized by argonmagnetron sputtering on microscope slides. Some of them are encapsulated with a thin, transparent and non-photochromic diffusion-barrier layer of either Al2O3 or Si3N4. Ion beambased methods prove that these protective diffusion barriers are stable and free from pinholes, with thicknesses of only a few tens of nanometers. Optical spectrophotometry reveals that the photochromic response and relaxation time for bothprotected and un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Therefore, the metallization is confirmed under an H- and O-free atmosphere. Furthermore, it has recently been reported that YO x H y coated with Al 2 O 3 or Si 3 N 4 also shows the photoresponse . Consequently, the mechanism involving the loss and replenishment of H and/or O atoms is excluded from consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the metallization is confirmed under an H- and O-free atmosphere. Furthermore, it has recently been reported that YO x H y coated with Al 2 O 3 or Si 3 N 4 also shows the photoresponse . Consequently, the mechanism involving the loss and replenishment of H and/or O atoms is excluded from consideration.…”
Section: Resultsmentioning
confidence: 99%
“…The protective ALD coating changes the kinetics of bleaching from the first-order behavior we normally find. , We observe this effect also when comparing coated and uncoated GdH 3–2 x O x films (Figure S15). Whether or not encapsulation of REH 3–2 x O x thin films influences the photochromic effect is debated but is outside the scope of this work. We suppose that the ALD-coated films are better described by a series of processes with no single rate constant or by kinetics of a different order.…”
Section: Discussionmentioning
confidence: 99%
“…Photochromic materials feature a change in optical properties as a response to electromagnetic irradiation, which makes them enticing for a vast number of applications in different fields like smart windows, sensors, and ophthalmology. , Oxygen-containing yttrium hydride (YHO) along with some other oxygen-containing rare-earth metal hydrides (ScHO, NdHO, GdHO, DyHO, and ErHO) , were shown to feature a color-neutral photochromic effect at ambient conditions. The effect persists when the films are coated with a protective layer (Al 2 O 3 or Si 3 N 4 ) enabling their utilization in multilayered structures . Thin films of YHO are typically produced by either reactive magnetron sputtering or e – beam evaporation of yttrium dihydride followed by oxidation and they show photochromic properties in a range of chemical compositions with the oxygen to yttrium ratio δ of 0.5 < δ < 1.5 .…”
Section: Introductionmentioning
confidence: 99%